2019
DOI: 10.1108/nfs-05-2019-0157
|View full text |Cite
|
Sign up to set email alerts
|

Flaxseeds (L. Usitatissimum) attenuates blood pressure, acetylcholinesterase activity and oxidative stress in ouabain-induced hypertension in normal Wistar rats

Abstract: Purpose The purpose of this study is to evaluate the effects of flaxseed (L. usitatissimum [Linn]) on blood pressure, redox status markers and acetylcholinesterase enzyme activity in ouabain-induced hypertension in normal Wistar rats. Design/methodology/approach Male Wistar rats weighing 250 ± 7 g (n = 24) fed with an experimental diet containing 20 per cent casein were divided into three groups (n = 8) and received a daily subcutaneous injection of either 0.9 per cent saline solution (T group) or 10 µg/kg/d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Also, Zeggwagh et al (2014) found that herba-alba at 50, 100 and 200 mg/kg produced a dose dependent decline in arterial blood pressure where an obvious decline in heart regularity occurred after Artemisia herba alba injection at the doses of 100 and 200 mg/kg. Moreover, Berzou et al (2019) proved that the treatment with flaxseed (common flax or linseed) had a significant effect in decreasing systolic, DBP, mean arterial pressure and the heart rate in hypertensive rats. Furthermore, Harrat et al (2019) stated that prickly pear treatment decreased arterial diastolic and systolic pressures, thiobarbituric acid reactive substances and lipid hydroperoxide contents in liver, adipose tissue, muscle and kidney.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Zeggwagh et al (2014) found that herba-alba at 50, 100 and 200 mg/kg produced a dose dependent decline in arterial blood pressure where an obvious decline in heart regularity occurred after Artemisia herba alba injection at the doses of 100 and 200 mg/kg. Moreover, Berzou et al (2019) proved that the treatment with flaxseed (common flax or linseed) had a significant effect in decreasing systolic, DBP, mean arterial pressure and the heart rate in hypertensive rats. Furthermore, Harrat et al (2019) stated that prickly pear treatment decreased arterial diastolic and systolic pressures, thiobarbituric acid reactive substances and lipid hydroperoxide contents in liver, adipose tissue, muscle and kidney.…”
Section: Discussionmentioning
confidence: 99%